STRUKTUR KOMUNITAS GULMA PADA PERKEBUNAN KELAPA SAWIT ( Elaeis guinnensis jacq ) DI DESA KEPENUHAN TENGAH KABUPATEN ROKAN HULU SEBAGAI RANCANGAN BUKU SAKU BIOLOGI SMA KELAS X - Nurul Annisya; Yuslim Fauziah; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the structure of weed communities on oil palm plantations in the village of Kepuhi Tengah in Rokan Hulu Regency and the design of learning resources in the form of pocket books. The study was conducted on oil palm plantations in the village of Kepuhi Tengah in Rokan Hulu Regency and in the Biology Education Laboratory of the Teaching and Education Faculty of the University of Riau in August to September 2019. This study used a survey method. By taking a purposive random sampling aside and considering the age factor of oil palm plantations, and determining the plot is done randomly through a lottery. The parameters in the study are, important value index, diversity index, composition, and similarity index. The parameters include soil moisture, soil temperature, soil pH and light intensity. The results obtained by the Community Structure of weeds in oil palm plantations found the level of weed diversity consisting of 47 species of weeds classified into 35 families dominated by Paspalum dimidiatum of 2217 individuals and the highest proportion of weeds in oil palm plantations was the Melastomataceae family of 19.05% . Weed Diversity Index ranged from 1.74-2.33. The highest importance index was found at station II, Lophatherum gracile species with NP 78.12% and the lowest was found at station I, Drynaria quercifolia with NP 0.76%. Weed similarity index was found to be relatively low, ranging between 029-0.55. The results of the study have been made as a source of biology class X high school learning on ecosystem material in the form of pocket books.Key Words: Pocket Book, Weed at Oil Palm Plantation, Community Structure, Composition.